Mechanisms and Deployment of Resistance in Trees to Insects - Wagner, Michael R.; Clancy, Karen M.; Lieutier, Fran©ʹois.; Paine, Timothy D. (Springer Netherlands, 2002)
Mechanisms and Deployment of Resistance in Trees to Insects is a worldwide synthesis of tree resistance to insects. The contributions are by senior scientists and represent all the major forested regions of the world. The book constitutes a comprehensive treatment of the state of our knowledge on patterns of resistance by insect guilds and how this knowledge can be deployed to achieve the management of damaging forest insects. This book will serve as an essential reference book for all researchers and practitioners attempting to manage forest pests using genetic resistance.